The heart of the film writing love stories in screenplays - Whitcomb, Cynthia (New York Routledge, 2017)
"Most movies include a love story, whether it is the central story or a subplot, and knowing how to write a believable relationship is essential to any writer's skill set. Discover the rules and laws of nature at play in a compelling love story and learn and master them. Broken into four sections, The Heart of the Film identifies the critical features of love story development, and explores every variation of this structure as well as a diverse array of relationships and types of love. Author Cynthia Whitcomb has sold over 70 feature-length screenplays and shares the keys to her success in The Heart of the Film, drawing on classic and modern films as well as her own extensive experience"--Provided by publisher.
Includes index.
Keywords: Motion picture authorship; Television authorship; Romance fiction -- Authorship